PENGEMBANGAN BAHAN AJAR BOOKLET BERBASIS KEARIFAN LOKAL MASYARAKAT DESA PENGADANG PADA MATERI TERMOKIMIA - Violeta, Cornelia; Hairida, Hairida; Masriani, Masriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research and development aims to produce product booklet teaching materials based on the local wisdom of Pengadang Village communities on thermochemical material. This research was conducted from April to June 2018. The respondents were chosen through snowball sampling. Dayak chieftain as the community leader was taken as the primary respondent and the interview was done in semi-structured technique. The result show that there are Annona muricata L., Hibiscus rosa-sinensis L., Kalanchoe pinnata, Carica papaya L., Allium cepa L., Lansium domesticum, Stachytarpheta sp., Verbena sp., dan Blumea balsamifera (L.) DC. The result show Stachytarpheta sp., Allium cepa L., and Blumea balsamifera (L.) DC. have 100% cition frequency. The development booklet teaching materials based on the local wisdom of Pengadang Village communities on thermochemical material based on measures of research and development by Borg & Gall. Field test sample in this research was determined by purposive sampling. Data collected by using a feasibility product questionnaire and student response questionnaire to Booklet teaching materials based on the local wisdom of Pengadang Village communities on thermochemical material. Based on analysis  the results of the product feasibility product questionnaire CVR is 0,99 (Valid)  and CVI is 0,99 (Valid). Preliminary field testing results for usability level product obtained a percentage of 77,62% % with a high criteria for use. Main field testing results for usability level product obtained a percentage of 81,10 % with a highest criteria for use. Keywords : Booklet Teaching Material, Development, Local Wisdom